VILLAVERDE RICO, María José y CASTILLA URBANO, Francisco (dirs.) (2016): La sombra de la leyenda negra, Madrid: Tecnos. - Díaz Martín, José Manuel (Daimon Revista Internacional de Filosofia, 2017)
Reseña de VILLAVERDE RICO, María José y CASTILLA URBANO, Francisco (dirs.) (2016): La sombra de la leyenda negra, Madrid: Tecnos.